ANALYSING GENDER ROLE PERCEPTIONS IN INDIAN TELEVISION ADVERTISEMENTS: A STUDY IN MATHURA, UTTAR PRADESH - Suman, Sweta; Sharma, Reena (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The purpose of the study is to comprehend the perceptions of young people regarding the images, roles and to know the changing trends regarding women and men's portrayal in various advertisements in Mathura region. This study's novelty lies in shedding light on the impact of culturally bounded aspects of advertising and perception of youth in Mathura. It also aims to highlight shifts in youth perceptions before and after exposure to these ads, urging advertisers to promote gender equality and reflect societal realities more accurately. The study was conducted with the school students in Mathura based on gender, age, and interests, Uttar Pradesh, India, to find their perceptions and opinions regarding the roles, trends and depictions of males and females in advertisements on television. This exploration is facilitated through a semi-structured questionnaire and a knowledge inventory test. The age of the young audience preferred for the study is between 15-19 years. To understand that what youth knows about the gender roles while watching ads on television and what are their perceptions on the images, roles and portrayals of women and men in the Indian television ads. The study initially collected data on viewers' perceptions of gender roles in selected Indian TV ads during prime time (8-9 pm). Two channels with the highest TRP were chosen, and six frequently aired ads were selected. A sample of 40 respondents, evenly split between genders aged 15-19, underwent a knowledge inventory test. Findings revealed stereotypical portrayals, with women mostly depicted in domestic roles and highly objectified. Men were shown as breadwinners and occasionally in domestic settings. This study also offers new critical insights into advertising that still employs gender stereotypes, such as gender roles mainly associated with men, implying that empowered women must behave like men.